Pemberdayaan Nelayan Dijemaat GMIM Kapernaum Minanga Tiga Wilayah Pusomaen - Joseph, Altje (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2022)
The church is in the world with three tasks that is ally, serve and testify for glory God’s name andbe a blessing,in and outside church body itself.Church attendance not just service on the pulpit church or in the service ceremonial ones but have to touch all problems,struggle,church struggle from problems faced in the field economy, socialand cultural.In a struggle fight the conngregation served, with some church members those who work is a fiherman which is confronted with problems it’s poverty,income level, education the low one attached to fisherman and his family, then here church must play a role church empowerment special for labor fisherman and light boat fisherman. Based on background this then in the main formula the problem as follows : (1) how’s the profile fisherman, (2) why fisherman is at helples condition or classified as poor?,(3) how to empower fiherman?As for the purpose study is describe fisherman profile, identify factorrs the causes church fiherman classified as poor, find way out fisherman empowerment congregation.The methodology that will be usengin this research is the qualitative reserch method.The resu of this research show that there is a relationship cooperation between church and goverment in empowering fisherman, but effort who have been obssesed depends on the fishermen themselves,when they initiative want to try and work empower himself associted with language work fisherman who are in the field.